2002
DOI: 10.2134/jeq2002.1893
|View full text |Cite
|
Sign up to set email alerts
|

Lead Phytoextraction from Contaminated Soil with High‐Biomass Plant Species

Abstract: In this study, cabbage [Brassica rapa L. subsp. chinensis (L.) Hanelt cv. Xinza No 1], mung bean [Vigna radiata (L.) R. Wilczek var. radiata cv. VC-3762], and wheat (Triticum aestivum L. cv. Altas 66) were grown in Pb-contaminated soils. Application of ethylenediaminetetraacetic acid (EDTA) (3.0 mmol of EDTA/kg soil) to the soil significantly increased the concentrations of Pb in the shoots and roots of all the plants. Lead concentrations in the cabbage shoots reached 5010 and 4620 mg/kg dry matter on Days 7 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
162
1
8

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 301 publications
(180 citation statements)
references
References 45 publications
9
162
1
8
Order By: Relevance
“…This research was funded by a grant from the Natural Sciences and Engineering Mullen verbascum Pichtel et al 2000 Triticum aestivum Huang et al 1997;Shen et al 2002;Cui et al 2004 Nicotiana glauca Barazani et al 2002Vetiveria zizanoides Xia 2004 N. rustica Vigna radiata Shen et al 2002 Paspalum notanum Xia 2004 Zea mays Chen et al 2004;Weissenhorn et al 1995 …”
Section: Acknowledgments 506mentioning
confidence: 99%
See 1 more Smart Citation
“…This research was funded by a grant from the Natural Sciences and Engineering Mullen verbascum Pichtel et al 2000 Triticum aestivum Huang et al 1997;Shen et al 2002;Cui et al 2004 Nicotiana glauca Barazani et al 2002Vetiveria zizanoides Xia 2004 N. rustica Vigna radiata Shen et al 2002 Paspalum notanum Xia 2004 Zea mays Chen et al 2004;Weissenhorn et al 1995 …”
Section: Acknowledgments 506mentioning
confidence: 99%
“…It has been reported that 489 chelating agents enhance plant HM uptake Chen et al 2003b; Cui et al 490 2004;Jiang and Yang 2004). It has also been shown that hyperaccumulators often tolerate and 491 take up higher HM levels compared to non-hyperaccumulator species (Delorme et al 2001; 492 Marchiol et al 2004;Shen et al 2002). Moreover, the correlation values fitted for plant tissue or 493 study type were mostly not different from the unfitted values, and therefore account for only a 494 small proportion of the variance in our study.…”
mentioning
confidence: 99%
“…Most hyperaccumulators, such as Thlaspi, Urtica, Chenopodium, Polygonum sachalase and Alyssim are characterized by slow growth and low-biomass production, which make these plants impractical for use in phytoextraction in the field (Mulligan et al, 2001;Puschenreiter et al, 2001). For this reason, more recent research projects on phytoextraction have focused on high biomass crop species, such as maize (Zea mays), peas (Pisum sativum), oats (Avena sativa), barley (Hordeum vulgare) and Indian mustard (Brassica juncea), and on relevant plant husbandry and soil management practices to enhance the metal uptake of these high biomass species (Blaylock et al, 1997;Huang et al, 1997;Ebbs and Kochian, 1998;Shen et al, 2002;Chen et al, 2004a). Although several conditions must be met in order for phytoremediation to be effective, the bioavailability of metals to plant roots is considered to be a critical requirement for plant uptake to occur (Kayser et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Soil factors such as pH, cation exchange capacity, or organic matter content play an important role in successful soil remediation processes. To increase metal availability, a number of chelates such as EDTA (ethylenediaminetetraacetic acid), CDTA (trans -1, 2 -diaminocyclohexane -N, N, N', N'-tetraacetic acid), EGTA [ethyleneglycol -bis (ß -aminoethyl ether), N, N, N', N-tetraacetic acid], and EDDHA [etylenediamine-di (ohydroxyphenylacetic acid)]) have been used to desorb metals from the soil matrix into soil solution to facilitate the transport of metals into xylem, and increase the translocation of metals from the roots to shoots of some fast-growing, high-biomass-producing plants (Blaylock et al, 1997;Huang et al, 1997;Cooper et al, 1999;Wu et al, 1999;Shen et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Whilst there are strict regulations in many developed countries on the use and release of lead into the environment, particularly, on the former use of lead in petrol as an anti-knock additive (Kaysi et al, 2000;Kummer et al, 2009), this is not the case with most developing countries where leaded petrol is still in use (Gwilliam, 2003). Over the years the emphasis has been on leaded fuel (Oudijk, 2010;Nriagu et al, 1996;Romieu et al, 1992), but there are many other activities that release Pb into the environment particularly in the urban/industrial setting: activities such as metal mining, smelting and processing, the use of Pb in lead-acid batteries, pigments, alloys, lead wool, chemical manufacturing, cables, solders, plumbing components, food cans, coal combustion, lead based paint (including that in road markings), and industrial waste (Ajmore-Marsan and Biasioli, 2010;Brown and Longoria, 2010;De Silva et al, 2016;Laidlaw and Taylor, 2011;Mielke et al, 2010;Shen et al, 2002). Studies have shown that the Pb retained in soil/dust because of anthropogenic activity typically occurs in highly bioavailable, exchangeable and carbonate forms, whereas, Pb retained because of natural occurrence is often found in residual or lessbioavailable forms (Chlopecka et al, 1997;Cox et al, 2013;Palumbo-Roe et al, 2013;Pelfrêne et al, 2012;Laidlaw and Filippelli, 2008;Reis et al, 2014;Ruby et al, 1994).…”
Section: Introductionmentioning
confidence: 99%